Method of Collecting Exchange Rates for the Calculation of the Value of the SDR for the purposes of Rule 0-2(a). - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2016)
This paper proposes modifications to the method of collecting exchange rates for the calculation of the value of the SDR for the purposes of Rule O-2(a). The value of the SDR in terms of the U.S. dollar is determined daily as the sum of the equivalents in U. S. dollar values of the amounts of the currencies that comprise the SDR valuation basket (as provided in Rule O-1), calculated on the basis of exchange rates established in accordance with procedures decided from time to time by the Fund.1 The current procedures are set out in Decision No. 6709-(80/189) S, as amended by Decision No. 12157-(00/24) S, March 9, 2000 (see Annex), which specifies the method for collecting exchange rates for this purpose. Under these procedures, the relevant currency amounts are converted into U.S. dollars using daily exchange rates that are provided to the Fund by the Bank of England (BoE). If rates cannot be obtained from the BoE, they are provided by the Federal Reserve Bank of New York (FRBNY) and, if not available there, by the European Central Bank (ECB). The BoE, FRBNY, and ECB intend to rely on a new, more robust methodology to provide exchange rates to the Fund after November 1, 2016, and the proposed modifications reflect these changes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United States